2022
DOI: 10.1101/2022.05.26.22275532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A global systematic analysis of the occurrence, severity, and recovery pattern of long COVID in 2020 and 2021

Abstract: ImportanceWhile much of the attention on the COVID-19 pandemic was directed at the daily counts of cases and those with serious disease overwhelming health services, increasingly, reports have appeared of people who experience debilitating symptoms after the initial infection. This is popularly known as long COVID.ObjectiveTo estimate by country and territory of the number of patients affected by long COVID in 2020 and 2021, the severity of their symptoms and expected pattern of recoveryDesignWe jointly analyz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 96 publications
0
43
0
1
Order By: Relevance
“…However, a recent study by the IHME quantified long COVID parameters across three separate symptom groups (cognitive difficulty, fatigue, and shortness of breath). 26 In a supplementary analysis (Appendix 7), we calculated long COVID morbidity with the IHME's estimates, and found comparable results.…”
Section: Morbidity Estimatesmentioning
confidence: 76%
See 2 more Smart Citations
“…However, a recent study by the IHME quantified long COVID parameters across three separate symptom groups (cognitive difficulty, fatigue, and shortness of breath). 26 In a supplementary analysis (Appendix 7), we calculated long COVID morbidity with the IHME's estimates, and found comparable results.…”
Section: Morbidity Estimatesmentioning
confidence: 76%
“…Duration was applied differentially by acute COVID-19 severity, based on recent findings by Wulf Hansen et al, who reported a median duration of symptoms for community infections of 4 months, and 8.9 months for previously hospitalised cases. 26 Exceptions to this have been applied to psychological symptoms, for which a shorter duration is estimated, as well as for children (see Table 2). 18,19,27…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main symptoms include extreme tiredness, shortness of breath, chest pain or tightness and “brain fog” (that is problems with memory and concentration), as well as difficulty sleeping, heart palpitations, dizziness and joint pain. Persistence of anosmia and dysgeusia [ 9 ] or neuropsychiatric complications are also possible [ 10 , 11 , 12 , 13 ]. Therefore, the increasing importance of long COVID symptoms and burden, led the WHO organization to plan several international meetings with experts reaching a consensus on a definition and reporting details and the subtypes and case definitions of this condition [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Many patients experience manifestations that persist following acute COVID-19 or with onset after the acute period, affecting various organ systems. [2][3][4][5] These manifestations, when not explained by another cause, are part of the broader syndrome of Post Acute Sequelae of SARS-CoV2 Infection (PASC; colloquially referred to as Long COVID). The rate of newly diagnosed psychiatric disease has been found to be significantly increased in patients following COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%